A Study on the Word-Formation Logic of Tomato Names: From a Cross-Linguistic Perspective Based on Morphological Association and Source Labeling (Journal of humanities and social sciences exploratio, 2025)
This paper takes the names of tomatoes as the research object, based on the dual perspectives of morphological association and source labeling, and combines philological, linguistic, and cross-cultural research methods to explore their word-formation logic and cross-linguistic evolution patterns. The study finds that Chinese terms such as "xihongshi" and "fanqie"  follow a dual-track model of "source label (west, foreign, overseas) + morphological analog (persimmon, /eggplant)", which not only achieves cognitive domestication through analogy with local plants but also records the spatiotemporal trajectory of dissemination through prefix morphemes. In the diachronic dimension, the evolution of the prefixes "hu- ", "fan- ", "yang- ", and "xi- " outlines the spatial shift of China's foreign exchanges. At the synchronic level, cross-linguistic comparisons among Chinese, Japanese, Korean, etc., reveal three typical naming paradigms: meaning-based labeling, pure transliteration, and morphological description. From a philological perspective, the form-meaning evolution and semantic generalization of the character "shi"  confirm the cognitive preference for "feature compounding" in Chinese plant naming. This study not only reveals the linguistic coding wisdom behind the naming of foreign crops but also uses micro-etymology as an entry point
Keywords: word-formation logic; morphological association; source labeling; cross-linguistic comparison